Mechanism of Strengthening Social and Labor Potential of Sustainable Development - Novikova, Olga; Ostafiichuk, Yaroslav; Khandiі Olena (Problemy Ekorozwoju, 2019)
The article considers the conceptual basis for strengthening social and labor potential of sustainable development in the context of economic efficiency and social justice. The essence of the categories social potential, social capital and social imperative in their interrelation with the social and labor sphere of society with the account of the needs of sustainable development is specified. Strengthening of social potential is considered as a complex of actions in such areas as education, culture, health care, economic and social spheres, social relations. The paper focuses on strong interconnections work – employment – labor potential – social potential – human development – sustainable development. A mechanism of strengthening social and labor potential through the transformation of employment in the context of the paradigm of sustainable development is suggested.